Pathological complete response to conversion therapy for lung adenocarcinoma with brain metastasis: a case report - Ran, Xingqiang; Luo, Tao; Xiong, Jie; Fu, Maoyong (Frontiers in Oncology, 2025)
Lung cancer is the leading cause of cancer mortality worldwide. Fortunately, the advent of precision medicine, which includes targeted therapy and immunotherapy, has significantly improved the survival rates of patients with locally advanced lung cancer. This article reports on a case of stage IVB (cT2bN1M1c1) non-small cell lung cancer (NSCLC) with brain metastases harboring compound mutations in epidermal growth factor receptor (EGFR) exon 21 Leu858Arg and mitogen-activated protein kinase 1 (MEK1) exon 3 lle112Thr and with a high program death ligand 1 (PD-L1) expression that successfully underwent radical lung cancer surgery following combined therapy. We report on a case of a 60-year-old man diagnosed preoperatively with stage IVB adenocarcinoma of the left upper lung (cT2bN1M1c1) who was diagnosed with multiple brain metastases. After multidisciplinary discussion, it was decided to administer targeted therapy with furmonertinib, chemotherapy with pemetrexed and lobaplatin, and immunotherapy with tislelizumab. Following 2 months of treatment, tumor assessment showed partial response (PR). After 11 months, assessment showed a PR of all lung lesions and complete response of the brain lesions, making the patient eligible for surgery. Finally, the patient underwent video-assisted thoracoscopic left upper lobectomy + mediastinal lymphadenectomy. Postoperative pathology confirmed complete response, and the patient continued adjuvant therapy with furmonertinib. For patients with metastatic advanced NSCLC, systemic treatment involving chemotherapy plus immunotherapy and targeted therapy is expected to become one of the options. Moreover, it is likely to achieve successful conversion surgery and further efficacy after combined therapy.